2022
DOI: 10.1186/s12885-022-09607-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy for meningiomas – a decision-making analysis

Abstract: Background The management of meningiomas is challenging, and the role of postoperative radiotherapy is not standardized. Methods Radiation oncology experts in Swiss centres were asked to participate in this decision-making analysis on the use of postoperative radiotherapy (RT) for meningiomas. Experts from ten Swiss centres agreed to participate and provided their treatment algorithms. Their input was converted into decision trees based on the obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…51 At present, postoperative radiotherapy is typically reserved for when there is evidence of tumor regrowth on follow-up imaging and there remains uncertainty regarding the efficacy of immediate adjuvant radiotherapy for WHO grade II tumors. 49,52,53 This question is currently the subject of two ongoing randomized control trials which will be instructive in guiding the future management of such patients. 54,55 In summary, our data demonstrate that 46% of SBM in this cohort demonstrated recurrence during a median period of follow-up of 11.25 years.…”
Section: Results In the Context Of The Literaturementioning
confidence: 99%
“…51 At present, postoperative radiotherapy is typically reserved for when there is evidence of tumor regrowth on follow-up imaging and there remains uncertainty regarding the efficacy of immediate adjuvant radiotherapy for WHO grade II tumors. 49,52,53 This question is currently the subject of two ongoing randomized control trials which will be instructive in guiding the future management of such patients. 54,55 In summary, our data demonstrate that 46% of SBM in this cohort demonstrated recurrence during a median period of follow-up of 11.25 years.…”
Section: Results In the Context Of The Literaturementioning
confidence: 99%
“…Different organizations have different views on how to treat atypical meningiomas, with some preferring treatment with radiation therapy after GTR, while others preferring radiation therapy alone 23 . NCCN and EANO guidelines recommend PORT for incompletely resected Grade II tumors 8,26 . The randomized trial ROAM/EORTC demonstrated a clinical benefit of PORT for recurrent atypical meningiomas after complete surgery 27 .…”
Section: Discussionmentioning
confidence: 99%
“…23 NCCN and EANO guidelines recommend PORT for incompletely resected Grade II tumors. 8,26 The randomized trial ROAM/EORTC demonstrated a clinical benefit of PORT for recurrent atypical meningiomas after complete surgery. 27 Prospective clinical trials are still needed to overcome this uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations